2011
DOI: 10.1371/journal.ppat.1002413
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Regulation of the Innate Immune Response and Apoptosis Occurs via the Product of the Alternative Open Reading Frame 4

Abstract: Small RNA viruses have evolved many mechanisms to increase the capacity of their short genomes. Here we describe the identification and characterization of a novel open reading frame (ORF4) encoded by the murine norovirus (MNV) subgenomic RNA, in an alternative reading frame overlapping the VP1 coding region. ORF4 is translated during virus infection and the resultant protein localizes predominantly to the mitochondria. Using reverse genetics we demonstrated that expression of ORF4 is not required for virus re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
250
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(265 citation statements)
references
References 81 publications
10
250
2
3
Order By: Relevance
“…Murine NoV research suggests that IFN-g and other Th-1 cytokines are important for limiting viral replication [26,27]. However, murine NoV is able to suppress type 1 IFN production [28]. In our study, we observed no significant elevation of IFN-a2, a type-1 IFN, post-challenge, suggesting that human NoV may be able to act similarly.…”
Section: Discussioncontrasting
confidence: 53%
“…Murine NoV research suggests that IFN-g and other Th-1 cytokines are important for limiting viral replication [26,27]. However, murine NoV is able to suppress type 1 IFN production [28]. In our study, we observed no significant elevation of IFN-a2, a type-1 IFN, post-challenge, suggesting that human NoV may be able to act similarly.…”
Section: Discussioncontrasting
confidence: 53%
“…Telomeres serve an important role in maintaining cellular chromosome stability and activity in the cells of various species (6). In the present study, TERT overexpression significantly promoted the growth of HT1080 cells, while TERT knockdown significantly inhibited growth.…”
Section: Discussionsupporting
confidence: 58%
“…In these systems, it is postulated that the virus may induce apoptosis to expand the window of time for virus replication, and caspase inhibitors reduce MNV replication (43). However, the best characterized noroviral or calicivirus proteins that regulate or are affected by apoptosis [the ORF1 encoded polyprotein of MNV (44), the unique VF1 protein of MNV (45), and the leader of the capsid protein of FCV (46)] are either different or not expressed from the HuNoV genome, and therefore, the mechanism of CPE induction for HuNoV remains to be determined. Several of the HuNoV nonstructural proteins could be involved.…”
Section: Discussionmentioning
confidence: 99%